Evaluation of impact in the sport specialties in postgraduate courses. Theoretical Fundamentals - Sara Maria Mena Morejón; Lázaro de la Paz Arencibia; Yolainy Govea Díaz; Giraldo Machuat Santana (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2019)
The present work deals with the theoretical referents to be considered for the evaluation of impact in postgraduate specialties, in the high performance sports of the Cuban sports system. The bibliographic study from the precursors to the present, deals with the conceptualization of evaluation, the evaluation of performance, and its relation with the evaluation of impact. The use of investigative methods of the empirical level such as the documentary analysis, the survey, the group interview and the criterion of experts, allowed to build a logical relationship to fulfill the proposed objective that consists on establishing the general theoretical positions for the impact evaluation. In postgraduate specialties programs for high performance sport in Cuba.